443 Participant demographics and disparities in ovarian cancer clinical trials. (13th November 2020) - Howell, E; Spinosa, D; Williams, D; Watson, C; Akinyemiju, T; Previs, R
Abstract : Background: Clinical trials comprise the cornerstone of advancing care for patients with ovarian cancer. Diverse populations of trial participants are essential to ensuring generalizability of results. To date, no prior study has aggregated all publicly available ovarian cancer clinical trials or analyzed the demographic makeup of participants enrolled in these trials. Methods: We evaluated all interventional therapeutic ovarian cancer trials registered to ClinicalTrials.gov that enrolled at US sites. Data were captured regarding study phase, enrollment sites, outcome metrics, and study population. Results: Our search identified 313 studies, of which 262 had published results for evaluation. To assess race and ethnicity, studies were then limited to the 217 studies enrolling at purely U.S. sites. Mean number of locations per study was 13.2 (range 1–390); mean number of participants per trial was 70.1 (range 1–4312). Only 75 studies (34.6%) reported participant race. Most studies enrolled predominantly white patients. Greater than 75% of enrollees were white, and 20 studies (26.7%) enrolled only white participants. Even fewer trials (52 studies, 19.8%) reported ethnicity data. The majority of studies enrolled predominantly Non-Hispanic/Latino participants. Greater than 75% of participants were Non-Hispanic/Latino, with 24 studies (46.2%) enrolling 100% Non-Hispanic/Latino patients. Conclusions: Few trials report the demographics of their participants, limiting the ability to assess generalizability. Most therapeutic trials for ovarian cancer patients enroll exclusively white and/or non-Hispanic/Latino participants. Further work is needed to elucidate the barriers to enrollment of diverse patient populations in order to ensure equity in the treatment of patients with ovarian cancer.